Barriers to Sustainable Construction Implementation in Makassar: A Comparative Study of State-Owned and Private Contractors - Ikhsan; Riska Ayu Melyanti Sabang (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Achieving sustainability in construction projects requires active involvement from all stakeholders in implementing environmentally responsible techniques and materials throughout the project lifecycle. This study aims to identify and analyze the barriers to sustainable construction implementation from the perspectives of both state-owned and private contractors. A purposive sampling technique was employed to determine the study participants. Using the Interpretive Structural Modeling (ISM) approach, this research reveals key hierarchical barriers within each contractor group. For state-owned contractors, the most prominent barriers include A1 (Lack of knowledge and standards), A5 (Project manager incompetence), and A6 (Limited access to sustainable materials and technology). In contrast, private contractors identified A1 (Lack of knowledge and standards), A2 (Poor design practices), and A4 (Lack of communication between project stakeholders) as the most critical barriers. These findings suggest that different strategies and policy interventions are needed to address context-specific barriers in order to accelerate the adoption of sustainable construction practices across sectors.